De la retórica a la ficción - Leonardo Funes (Medievalista)
The incorporation into the chronistic narrative of direct speech has been a historiographical resource from classic Antiquity. The conventional acceptance of textual citation words pronounced by historical characters was included in the "historiographical" pact (the public accepts the poetical or rhetorical license as an expression of the most profound dimension of historical truth).However, when Alphonsine and Post-Alphonsine chroniclers began to incorporate dialogues in direct speech, this convention was a challenge for the claim to truth made by chronicle narratives.This article aims to trace the evolution of the use of direct speech from Alphonsine historiography to the historiography of John II of Castile, in order to evaluate its impact on the historical and fictional narrative forms.